Electrical Characteristic of Polymer-Insulated Rail Brackets of the Light Rail Transit Subjected to Lightning Induced Overvoltage - Abd Rahman F.A.; Abidin Ab Kadir M.Z.; Ungku Amirulddin U.A.; Osman M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electrolysis; Glass fibers; Light rail transit; Lightning protection; Reinforced plastics; Reinforcement; DC transit; Electrical characteristic; EMTP-RV; Fourth rail; Glass reinforced plastics; Indirect lightning; Lightning strikes; Lightning-induced overvoltages; Performance; Surge arresters; Surge protection